Replacement of synthetic astaxanthin with microalgal and bacterial sources: Effects on growth, colouration, nutrient retention, antioxidant capacity, and gut microbiome of rainbow trout - Samantha Bezner; Mya Gowanlock; Xiang Cheng; Marcia Chiasson; David Huyben (Aquaculture, 2027)

Characterizing effects of tree mortality from wildfire and bark beetles using satellite observations of solar-induced chlorophyll fluorescence - Lewis Kunik; David R. Bowling; Brett Raczka; Jeffrey A. Hicke; Christian Frankenberg; Rui Cheng; Michèle R. Slaton; John C. Lin (Remote Sensing of Environment, 2026)

Is the association between PGE deposits and diamond provinces in ancient cratonic blocks linked to mantle overturns in the early earth? - David I. Groves; Wolfgang Maier; M. Santosh; Liang Zhang; Cheng-Xue Yang (Ore and Energy Resource Geology, 2026)

Fermentation-derived umami peptides from animal-based foods: Mechanistic insights, nutritional benefits, and technological innovations - Hira Nawazish; Che Shen; Ran Wang; Jingnan Lu; Jieshun Cheng; Hui-Min David Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

The impact of component interactions on fried flour products: synergistic regulation through dough mixing, resting and frying stages - Mengyue Li; Guifang Huang; Hao Cheng; David Julian McClements; Jianwei Zhao; Qing Hong; Zhenmin Liu; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2026)

Thaw hazards along major transportation corridors in the northern Da Xing'anling Mountains in Northeast China - Huijun Jin; Wenhui Wang; Jianjun Tang; Shanzhen Li; Shuai Huang; Zhengyun He; Yaohui Cheng; Guangyin Xue; Alexander N. Fedorov; Raul-David Şerban; Xiaoying Jin (Engineering Geology, 2026)

Pronounced drought and wet periods during the Maya Terminal Classic period reconstructed using stalagmite calcium isotopes - Daniel H. James; Harold J. Bradbury; Stacy A. Carolin; Sebastian F.M. Breitenbach; Hai Cheng; Ian J. Orland; Jason H. Curtis; Adam Hartland; Christina Gallup; Ola Kwiecien; Andrew J. Mason; Gideon M. Henderson; et al. (Earth and Planetary Science Letters, 2026)

Aufeis in a warming world: Global patterns, processes, and environmental implications - Shanzhen Li; Hongqi Mi; Xue Yang; Xiaoying Jin; Anyuan Li; Bo Wang; Aoxiang Yan; Zhengyun He; Shuai Huang; Zuwang Li; Jianjun Tang; Jingyan Xu; et al. (Earth-Science Reviews, 2026)

Persistently high oxidative burden of PM2.5 amidst declining mass concentration: Evidence from long-term observation in Shanghai - Yue Huang; Yuankai Xie; Wei Zhang; Lu Xu; Ming Hu; Cheng Huang; Qingyan Fu; Steven J. Campbell; Gang I. Chen; David C. Green; Jialiang Feng; Shunyao Wang (Environmental Pollution, 2026)

Source Transition and Health Implication of PM2.5-Bound Metals: Multi-year High-resolution Observation in a Coastal Megacity - Yanjie Lei; Ming Hu; Yuankai Xie; Anja H. Tremper; Yue Liu; Lan Hong; Xin Cheng; Cheng Huang; Qingyan Fu; Jialiang Feng; David C. Green; Longhua Wu; et al. (Atmospheric Environment, 2026)

Triple oxygen isotope analysis of cave drip waters: insights into hydrological processes and paleoclimatic reconstruction - Lijuan Sha; Qisheng Liang; Yunxia Li; David Domínguez-Villar; Lijun Tian; Baoyun Zong; Yajie Yang; Jun-Yun Li; Haiwei Zhang; Ting-Yong Li; Hai Cheng (Geochimica et Cosmochimica Acta, 2026)

Effects of medium- and long-chain triacylglycerol on sarcopenia under the different protein levels in aged male C57BL/6J mice - Xinyi Cheng; Chenyu Jiang; Jun Jin; Qingzhe Jin; David Julian McClements; Wei Wei; Xingguo Wang (Food Bioscience, 2026)

Feeding fodder beet (Beta vulgaris L.) versus pasture reduces methane emissions and nitrogen excretion in sheep - Xuezhao Sun; David Pacheco; Long Cheng; Sarah Maclean; Dongwen Luo; Peter H. Janssen (Animal Feed Science and Technology, 2026)

Large-scale avulsion of the lower Yellow River revealed by landscape evolution modeling - Xiang He; Xiaoping Yuan; Jun Cheng; David B. Kemp; Xianyan Wang; Zongmin Zhu; Junsheng Nie; Shucheng Xie (Earth and Planetary Science Letters, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Utilization of enzymes for improving fried flour products: Recent advances, applications, and regulations - Zihao Tu; David Julian McClements; Guifang Huang; Hao Cheng; Zhengyu Jin; Long Chen (Food Chemistry, 2026)

Achieving architecture upgrading through ceramic membrane separator-electrode: A strategy for enhancing siphon-driven tidal flow constructed wetland-microbial fuel cell - Cheng Tang; Yaqian Zhao; Chun Kang; David Morgan (Chemical Engineering Journal, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Effect of pH-shifting combined with ultrasound treatment on the physicochemical, structural, and gelation properties of oxidized pea protein isolate - Qian Li; Siying Liu; Yi Cao; Yujie Cheng; Xudong Yan; Jun Chen; Taotao Dai; Peiyi Shen; David Julian McClements; Jian Xu; Ruiyun Chen (Food Hydrocolloids, 2026)

Effects of wheat starch and gluten protein interaction on fried flour products during processing - Mengyue Li; Guifang Huang; Hao Cheng; David Julian McClements; Jianwei Zhao; Yun Ma; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2026)

Interpenetrating network hydrogels based on soy protein isolate and sanxan: Structure, mechanical properties, and freeze-thaw stability - Yue Zhao; Yuehan Shan; Hongjuan Wang; Zhao Zhang; Caili Wang; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Carbohydrate Polymers, 2026)

Recent Advances on anti-retrogradation technologies of starch-based foods - Wanyi Niu; Haoming Sun; David Julian McClements; Long Chen; Hao Cheng; Weihao Ye; Yi Wang; Yao Hu; Hao Xu (Trends in Food Science & Technology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Corn starch-soy protein isolate films reinforced by metal-phenolic networks: Properties and application for strawberry preservation - Hao Cheng; David Julian McClements; Hao Xu; Hangxin Zhu; Ruojie Zhang; Zipei Zhang; Zhengyu Jin; Long Chen (Food Chemistry, 2026)

Lactiplantibacillus plantarum SG053 and SG066 Enhance Nutritional Value of Soy Protein via Improved Essential Amino Acid Bioavailability - David Agus Setiawan Wibisono; Chiou-Yeong Saw; Der-Kai Lau; Wei-Jen Chen; Hui-Fang Chu; Cheng-Yen Liu; Chi-Fai Chau (Probiotics and Antimicrobial Proteins, 2026)

Short-chain fatty acid starch esters in food preservation: preparation technologies, functions and application - David Mahoudjro Bodjrenou; Dur E. Sameen; Cheng Li; Qiang Huang; Bin Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Comparative analysis of water-soluble pectin structures in orange and pomelo juices: Impact on cloud stability - Qian Li; Shangdong Yan; Jialu Huang; Yujie Cheng; Ruiyun Chen; David Julian McClements; Jian Xu; Peiyi Shen; Xudong Yan (Food Chemistry, 2025)

Structural characterization of water-soluble pectin in NFC orange juice during cloud destabilization - Shiying Yang; Jian Xu; Siying Liu; Yujie Cheng; Fengjiao Cai; Yanjun Zhang; David Julian McClements; Peiyi Shen; Qian Li (Food Chemistry, 2025)

Improvement of low-oil emulsion gel performance using interfacial engineering: Impact of pea protein-curdlan interfacial structure on freeze-thaw stability and in vitro digestion - Yuehan Shan; Yue Zhao; Hongjuan Wang; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Food Chemistry, 2025)

Oxidized corn starch-soy protein isolate films reinforced by Schiff base-metal phenolic networks: Properties and application for blueberry preservation - Hao Cheng; David Julian McClements; Hao Xu; Hangxin Zhu; Ruojie Zhang; Zipei Zhang; Zhengyu Jin; Long Chen (Food Packaging and Shelf Life, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Polydopamine-functionalized graphene for stabilizing starch-based 3D networks and synergistically enhancing film properties - Hao Xu; David Julian McClements; Yao Hu; Hao Cheng; Jinyi Wu; Xuan Wang; Zhengyu Jin; Long Chen (Carbohydrate Polymers, 2025)

Bottom‐Up Interactions in State‐Space Age‐Structured Models Using Mass‐Balance Dynamics - James T. Thorson; Kerim Y. Aydin; Matthew L. H. Cheng; Beatriz S. Dias; David G. Kimmel; Kasper Kristensen (Fish and Fisheries, 2025)
Age‐structured models are used worldwide to regulate fisheries. These models typically ignore top‐down interactions (predation affecting natural mortality) and bottom‐up interactions (consumption affecting individual growth, reproduction, or survival), whereas multispecies catch‐at‐age models often incorporate top‐down but not bottom‐up interactions. While Ecopath‐with‐Ecosim (EwE) incorporates both top‐down and bottom‐up interactions along with age‐structured dynamics, it is not typically fitted to age‐composition data. We extend Ecostate (a state‐space version of EwE) to incorporate age‐structured dynamics while fitting to age‐structured data and use this to illustrate how to add bottom‐up interactions to age‐structured models. Specifically, we add age‐structured dynamics and likelihood components for age‐composition and weight‐at‐age data while estimating residual variation in larval survival (recruitment deviations) and consumption (weight‐at‐age deviations). As a demonstration, we fit the model to biomass and age‐composition data for two commercial species (Alaska pollock and sablefish) in the Gulf of Alaska, including population dynamics for their major prey, while not fitting weight‐at‐age data so that it can be used for out‐of‐sample evaluation of model performance. The model can be viewed as a multispecies age‐structured model (e.g., estimating adult mortality rates, survey catchability and selectivity, and recruitment variation) and as a mass‐balance ecosystem model (e.g., estimating trophic position and weight‐at‐age based on forage consumption). The predicted weight‐at‐age is weakly correlated with independent measurements for pollock and sablefish but was improved when we incorporated forage biomass indices. We recommend that age‐structured models routinely explore the link between prey consumption and resulting size‐at‐age, whether using coupled predator–prey dynamics or simplifications that treat prey abundance as fixed data.

Thermodynamically constrained retrieval algorithm to estimate subpixel fire properties - Chenchong Zhang; Yuan Wang; Jun Wang; Amber Soja; Emily Gargulinski; David Peterson; Olga Kalashnikova; Bin Zhao; Yafang Cheng; Fangjun Li; Rajan Chakrabarty (Remote Sensing of Environment, 2025)

Effect of various natural cross-linking agents on the properties of corn starch/soy protein isolate composite films - Hao Cheng; David Julian McClements; Hao Xu; Zipei Zhang; Ruojie Zhang; Zhengyu Jin; Long Chen (Carbohydrate Polymers, 2025)

High-temperature dissolutive wetting: Role of solutal Marangoni convection in multiphase transport - Zhongfu Cheng; Youqing Sun; Yijie Liang; Shoufeng Yang; David Seveno; Muxing Guo (Chemical Engineering Journal, 2025)

Ice crystal structure melting: insights from molecular dynamics simulations - Ran Wang; Shaohong Cheng; David S.-K. Ting; Arash Raeesi; Sean McTavish; Annick D'Auteuil (Cold Regions Science and Technology, 2025)

Livestock excreta facilitate invasive weed establishment and dominance in pastures through physical niche creation and nutrient pulses - Qihong Yuan; Xincheng Li; Cheng Zhang; Tingting Tao; Han Y.H. Chen; David Johnson; Zhiwei Zhong; Wei Zhang; Shaoli Zhong; Xiao Sun (European Journal of Agronomy, 2025)

Corrigendum to “Development of a comprehensive food glycomic database and its application: Associations between dietary carbohydrates and insulin resistance” [Food Chemistry 473 (2025) 142977] - Christopher Suarez; Shawn Ehlers Cheang; Jules A. Larke; Jiani Jiang; Cheng-Yu Charlie Weng; Aaron Stacy; Garret Couture; Ye Chen; Nikita P. Bacalzo; Jennifer T. Smilowitz; J. Bruce German; David A. Mills; et al. (Food Chemistry, 2025)

A novel synergistic inhibition mechanism of pancreatic lipase by 2-mercaptobenzothiazole and stearic acid migrants from dairy contact rubbers - Yujie Wang; Juan Cheng; David Julian McClements; Jing Chen; Da Ma (Food Chemistry, 2025)

An endothelial specific mouse model for the capillary malformation mutation Gnaq p.R183Q - Patrick Smits; Leanna Marrs; Yu Sheng Cheng; Michal Ad; Sana Nasim; David Zurakowski; Joyce Bischoff; Arin K. Greene (Angiogenesis, 2025)

Sterilization of Channel Catfish (Ictalurus punctatus) via Overexpression of bax Gene Regulated by a Tet-off System in the Primordial Germ Cells - Zhi Ye; Ahmed Elaswad; Guyu Qin; Dongdong Zhang; Baofeng Su; Karim Khalil; Zhenkui Qin; Nermeen Y. Abass; Qi Cheng; Ramjie Odin; Khoi Vo; Nathan Backenstose; et al. (Marine Biotechnology, 2025)

Development of a comprehensive food glycomic database and its application: Associations between dietary carbohydrates and insulin resistance - Christopher Suarez; Shawn Ehlers Cheang; Jules A. Larke; Jiani Jiang; Cheng-Yu Charlie Weng; Aaron Stacy; Garret Couture; Ye Chen; Nikita P. Bacalzo; Jennifer T. Smilowitz; J. Bruce German; David A. Mills; et al. (Food Chemistry, 2025)

Impact of 2,4-di-tert-butylphenol on pancreatic lipase activity in emulsions: Multispectral, molecular docking, and in vitro digestion analysis - Weiyan Guan; Juan Cheng; David Julian McClements; Zongcai Tu; Jing Chen; Da Ma (Food Chemistry, 2025)

Seasonal dynamics of root growth and desiccation cracks and their effects on soil hydraulic conductivity - Yuliana Yuliana; Arwan Apriyono; Viroon Kamchoom; David Boldrin; Qing Cheng; Chao-Sheng Tang (Engineering Geology, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Achieving high energy harvest from a siphon boosted microbial fuel cell-constructed wetland system - Cheng Tang; Yaqian Zhao; Chun Kang; Yanhui Li; David Morgan (Journal of Water Process Engineering, 2025)

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Prehistoric human hand and footprints in Quesang on the central Tibetan Plateau from the Bølling-Allerød Interstadial - Yuhai Gao; David D. Zhang; Haiwei Zhang; Shengda Zhang; Teng Li; Shimin Chen; Chengcai Luo; Hai Cheng (Archaeological and Anthropological Sciences, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Challenges in assessing the effects of environmental governance systems on conservation outcomes - Raphael A. Ayambire; Trina Rytwinski; Jessica J. Taylor; Matthew W. Luizza; Matthew J. Muir; Cynthia Cadet; Derek Armitage; Nathan J. Bennett; Jeremy Brooks; Samantha H. Cheng; Jenny Martinez; Meenakshi Nagendran; et al. (Conservation Biology, 2025)
Effective governance is crucial for the success of conservation projects aimed at protecting wildlife populations and supporting human well‐being. However, few large‐scale, comprehensive syntheses have been conducted on the effects of different environmental governance types on conservation outcomes (i.e., biological and ecological effectiveness or effects of conservation on human well‐being), and clarity on the quantity and quality of evidence remains dispersed and ambiguous. We attempted a systematic map of the evidence on the effectiveness of different governance types to meet desired conservation outcomes in Africa, Asia, and Latin America. However, early in this effort, we observed a general lack of empirical research on the links between governance and conservation outcomes. To fill observed data gaps in the evidence base, we tried triangulating governance data from alternative sources (Protected Planet database) and pooling evidence from research conducted within the same conservation areas. Limited data were contained in the Protected Planet database, and governance types in conservation areas and landscapes were complex, making it difficult to use these approaches to assign governance types to conservation areas. To illustrate our observations from the failed systematic map attempt, we prepared a rapid evidence map that outlines a subset of the evidence base of articles linking governance types and governance principles with conservation outcomes. Only 3.2% (34 of 1067) of the articles we screened directly related conservation outcomes to governance type, and even fewer related governance principles to conservation outcomes. Based on our findings, we recommend improving the evidence base by supporting empirical research and increasing the availability and quality of governance data in freely accessible databases. These recommendations are critical for enhancing understanding of the role of governance in conservation projects and improving conservation outcomes.

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

Intelligent carrageenan-based composite films containing color indicator-loaded nanoparticles for monitoring fish freshness - Yahong Han; Mingrui Zhou; Jiajie Deng; Cheng Cheng; Zihan Xu; Wenfu Hou; Yang Yi; David Julian McClements; Shuai Chen (Food Packaging and Shelf Life, 2025)

Pearl-inspired functional biomaterials: Review of their preparation, characterization, and application in food packaging - Jiaqi Zhong; Hao Cheng; David Julian McClements; Zipei Zhang; Ruojie Zhang; Hui Zhou; Wu Wang; Jianwei Zhao; Zhengyu Jin; Long Chen (Trends in Food Science & Technology, 2024)

Fabrication of high internal phase emulsions (HIPEs) using pea protein isolate-hyaluronic acid-tannic acid complexes: Application of curcumin-loaded HIPEs as edible inks for 3D food printing - Zhiying Li; Liwen Zhang; Yuehan Shan; Yue Zhao; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Food Chemistry, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Extended aerosol and surface characterization from S5P/TROPOMI with GRASP algorithm. Part II: Global validation and Intercomparison - Cheng Chen; Pavel Litvinov; Oleg Dubovik; Lukas Bindreiter; Christian Matar; David Fuertes; Anton Lopatin; Tatyana Lapyonok; Verena Lanzinger; Andreas Hangler; Michael Aspetsberger; Martin de Graaf; et al. (Remote Sensing of Environment, 2024)

Extended aerosol and surface characterization from S5P/TROPOMI with GRASP algorithm. Part I: Conditions, approaches, performance and new possibilities - Pavel Litvinov; Cheng Chen; Oleg Dubovik; Lukas Bindreiter; Christian Matar; David Fuertes; Anton Lopatin; Tatyana Lapyonok; Verena Lanzinger; Andreas Hangler; Michael Aspetsberger; Martin de Graaf; et al. (Remote Sensing of Environment, 2024)

Utilization of diverse probiotics to create human health promoting fatty acids: A review - Kuang He; Hao Cheng; David Julian McClements; Zhenlin Xu; Man Meng; Yidong Zou; Guanxiong Chen; Long Chen (Food Chemistry, 2024)

Multiple approaches for heavy metal contamination characterization and source identification of farmland soils in a metal mine impacted area - Shubin Zhou; Qiuming Cheng; David C. Weindorf; Biying Yang; Zebin Gong; Zhaoxian Yuan (Applied Geochemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Monacolin-K loaded MIL-100(Fe) metal–organic framework induces ferroptosis on metastatic triple-negative breast cancer - Chien-Hui Yu; Glemarie C. Hermosa; An-Cheng Sun; Chia-Wen Kevin Wu; Mi-Tang Gao; Chun Wu; Hui-Min David Wang (Chemical Engineering Journal, 2024)

Tree stumps as passive samplers for trace metal dust deposition - Shubin Zhou; Zhaoxian Yuan; Qiuming Cheng; David C. Weindorf; Mark Patrick Taylor; Cynthia Faye Barlow; Jie Yang; Biying Yang; Abubakr M. Idris (Atmospheric Environment, 2024)

Investigation of oxygen packaging to maintain beef color stability and microbiology safety after periods of long-term superchilled storage - Jun Yang; Xue Chen; Xinxin Duan; Ke Li; Haijian Cheng; Ge Sun; Xin Luo; David L. Hopkins; Benjamin W.B. Holman; Yimin Zhang; Enliang Song (Meat Science, 2024)

Iron-retrofitted anaerobic baffled reactor system for rural wastewater treatment: Stable performance of nutrients removal with phosphorus recovery and minimal sludge production - Ruoning Zheng; Xiaohui Cheng; Xiaozhong Gao; Changyong Zhang; Xiang Cheng; T. David Waite (Bioresource Technology, 2024)

Linking Taiwan to the Cathaysia Block during the Cenozoic: Evidence from Pb isotopes in detrital K-feldspar - Ce Wang; Liangjie Wei; Cheng-Shing Chiang; David A. Foster; Heqi Cui; Ming Su (Global and Planetary Change, 2024)

An effective preserving strategy for strawberries by constructing pectin/starch coatings reinforced with functionalized eggshell fillers - Hao Xu; Yihao Huang; Kuang He; Ziqiang Lin; David Julian McClements; Yao Hu; Hao Cheng; Xinwen Peng; Zhengyu Jin; Long Chen (Food Chemistry, 2024)

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

District heating utilizing waste heat of a data center: High-temperature heat pumps - Pengtao Wang; Steve Kowalski; Zhiming Gao; Jian Sun; Cheng-Min Yang; David Grant; Philip Boudreaux; Shean Huff; Kashif Nawaz (Energy and Buildings, 2024)

Correction: Shear Strength and Consolidation Behaviour of Kaolin Clay Reinforced with a Granular Column Backfilled with Crushed Waste Glass - Danish Kazmi; Mehdi Serati; David J. Williams; Sebastian Quintero Olaya; Sadaf Qasim; Yi Pik Cheng; Athina Grizi; Akbar A. Javadi (Geotechnical and Geological Engineering, 2024)

Shear Strength and Consolidation Behaviour of Kaolin Clay Reinforced with a Granular Column Backfilled with Crushed Waste Glass - Danish Kazmi; Mehdi Serati; David J. Williams; Sebastian Quintero Olaya; Sadaf Qasim; Yi Pik Cheng; Athina Grizi; Akbar A. Javadi (Geotechnical and Geological Engineering, 2024)
Granular columns are commonly used for ground improvement. However, minimal research is presently available on the effect of backfill particle size on the geotechnical performance of granular column-reinforced soil. Geo-environmentally, using crushed waste glass (CWG) as a sustainable replacement for depleting traditional construction sands could offer a cleaner feedstock to backfill granular columns while helping recycle growing stockpiles of waste glass, potentially supporting the circular economy transition and decarbonisation of the construction industry. Given these multi-pronged motivations, this study investigated the shear strength and consolidation behaviour of kaolin reinforced with a CWG granular column. Three different particle size ranges (PSR) of CWG were discretely used to install a granular column in the kaolin bed, including fine (0.50–1.0 mm), medium (1.0–1.7 mm) and coarse (1.7–3.35 mm) particles with median particle sizes of 0.78 mm, 1.42 mm and 2.30 mm, respectively. The geocomposite containing a medium CWG column showed the highest increase in friction angle, increasing from 14.0° for kaolin only specimens to 20.7° for the geocomposites. Similarly, the consolidation behaviour of reinforced kaolin (geocomposites) was typically superior to that of kaolin only specimens. Notably, installing a coarse, medium or fine CWG column decreased the average compression index (C c ) of the geocomposites by almost 17%, 35% or 50%, respectively, compared to that of the kaolin only specimens. Given the promising results of this initial study, some suggestions are provided for future studies on assessing the application of CWG as an alternative backfill and sustainable geomaterial in granular column construction. Video abstract This internationally-partnered Video Abstract highlights the findings of the research study, indicating that crushed waste glass (CWG) could potentially serve as a sustainable geomaterial and be used as a replacement for traditional construction sand to backfill granular columns in clayey soils for ground improvement, helping reduce the unsustainable exploitation of sand resources and increasing waste glass recycling, potentially supporting the paradigm shift to a circular economy and contributing to decarbonisation of the construction industry.

Habitable planet to sustainable civilization: Global climate change with related clean energy transition reliant on declining critical metal resources - M. Santosh; David I. Groves; Cheng-Xue Yang (Gondwana Research, 2024)

Recent progress in the hydrophobic modification of starch-based films - Ziqiang Lin; Hao Cheng; Kuang He; David Julian McClements; Zhengyu Jin; Zhenlin Xu; Man Meng; Xinwen Peng; Long Chen (Food Hydrocolloids, 2024)

TDG prediction model improvement by analysis and validation of experiments on a dam model - Xiaolong Cheng; David Z. Zhu; Ran Li; Jingjie Feng; Hang Wang; Qing Yang; Kefeng Li; Pengcheng Li (Environmental Science and Pollution Research, 2024)

Biochemical, structural, and computational analyses of two new clinically identified missense mutations of ALDH7A1 - David A. Korasick; David P. Buckley; Alessandra Palpacelli; Ida Cursio; Elisabetta Cesaroni; Jianlin Cheng; John J. Tanner (Chemico-Biological Interactions, 2024)

Recent advances in the application of nanotechnology to create antioxidant active food packaging materials - Hao Cheng; Long Chen; David Julian McClements; Hao Xu; Jie Long; Jianwei Zhao; Zhenlin Xu; Man Meng; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2024)

Co-encapsulation of anthocyanin and cinnamaldehyde in nanoparticle-filled carrageenan films: Fabrication, characterization, and active packaging applications - Mingrui Zhou; Yahong Han; David Julian McClements; Cheng Cheng; Shuai Chen (Food Hydrocolloids, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Sitagliptin elevates plasma and CSF incretin levels following oral administration to nonhuman primates: relevance for neurodegenerative disorders - Yazhou Li; Kelli L. Vaughan; Yun Wang; Seong-Jin Yu; Eun-Kyung Bae; Ian A. Tamargo; Katherine O. Kopp; David Tweedie; Cheng-Chuan Chiang; Keith T. Schmidt; Debomoy K. Lahiri; Michael A. Tones; et al. (GeroScience, 2024)
The endogenous incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) possess neurotrophic, neuroprotective, and anti-neuroinflammatory actions. The dipeptidyl peptidase 4 (DPP-4) inhibitor sitagliptin reduces degradation of endogenous GLP-1 and GIP, and, thereby, extends the circulation of these protective peptides. The current nonhuman primate (NHP) study evaluates whether human translational sitagliptin doses can elevate systemic and central nervous system (CNS) levels of GLP-1/GIP in naive, non-lesioned NHPs, in line with our prior rodent studies that demonstrated sitagliptin efficacy in preclinical models of Parkinson’s disease (PD). PD is an age-associated neurodegenerative disorder whose current treatment is inadequate. Repositioning of the well-tolerated and efficacious diabetes drug sitagliptin provides a rapid approach to add to the therapeutic armamentarium for PD. The pharmacokinetics and pharmacodynamics of 3 oral sitagliptin doses (5, 20, and 100 mg/kg), equivalent to the routine clinical dose, a tolerated higher clinical dose and a maximal dose in monkey, were evaluated. Peak plasma sitagliptin levels were aligned both with prior reports in humans administered equivalent doses and with those in rodents demonstrating reduction of PD associated neurodegeneration. Although CNS uptake of sitagliptin was low (cerebrospinal fluid (CSF)/plasma ratio 0.01), both plasma and CSF concentrations of GLP-1/GIP were elevated in line with efficacy in prior rodent PD studies. Additional cellular studies evaluating human SH-SY5Y and primary rat ventral mesencephalic cultures challenged with 6-hydroxydopamine, established cellular models of PD, demonstrated that joint treatment with GLP-1 + GIP mitigated cell death, particularly when combined with DPP-4 inhibition to maintain incretin levels. In conclusion, this study provides a supportive translational step towards the clinical evaluation of sitagliptin in PD and other neurodegenerative disorders for which aging, similarly, is the greatest risk factor.

Bioplastic degradation and assimilation processes by a novel bacterium isolated from the marine plastisphere - Valérie Barbe; Justine Jacquin; Madeleine Bouzon; Adèle Wolinski; Gabrielle Derippe; Jingguang Cheng; Corinne Cruaud; David Roche; Stéphanie Fouteau; Jean-Louis Petit; Pascal Conan; Mireille Pujo-Pay; et al. (Journal of Hazardous Materials, 2024)

TDG generation in a ski-jump spillway with a fully or partial-flip bucket - Xiaolong Cheng; Ran Li; Jingjie Feng; David Z. Zhu; Kefeng Li (Journal of Environmental Management, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Crossflow flat solid oxide fuel cell (SOFC) semi-empirical modeling and the multi-fuel property based on a commercial 700 W stack - Junhan Cheng; Ralph Lavery; Christopher S. McCallum; Kevin Morgan; John Doran; Chunfei Wu; Kening Sun; David W. Rooney (Fuel, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Net greenhouse gas balance in U.S. croplands: How can soils be part of the climate solution? - Yongfa You; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; William D. Batchelor; Bo Cheng; Dafeng Hui; David Kicklighter; Xin‐Zhong Liang; Xiaoyong Li; Jerry Melillo; et al. (Global Change Biology, 2024)
Agricultural soils play a dual role in regulating the Earth's climate by releasing or sequestering carbon dioxide (CO 2 ) in soil organic carbon (SOC) and emitting non‐CO 2 greenhouse gases (GHGs) such as nitrous oxide (N 2 O) and methane (CH 4 ). To understand how agricultural soils can play a role in climate solutions requires a comprehensive assessment of net soil GHG balance (i.e., sum of SOC‐sequestered CO 2 and non‐CO 2 GHG emissions) and the underlying controls. Herein, we used a model‐data integration approach to understand and quantify how natural and anthropogenic factors have affected the magnitude and spatiotemporal variations of the net soil GHG balance in U.S. croplands during 1960–2018. Specifically, we used the dynamic land ecosystem model for regional simulations and used field observations of SOC sequestration rates and N 2 O and CH 4 emissions to calibrate, validate, and corroborate model simulations. Results show that U.S. agricultural soils sequestered Tg CO 2 ‐C year −1 in SOC (at a depth of 3.5 m) during 1960–2018 and emitted Tg N 2 O‐N year −1 and Tg CH 4 ‐C year −1 , respectively. Based on the GWP100 metric (global warming potential on a 100‐year time horizon), the estimated national net GHG emission rate from agricultural soils was Tg CO 2 ‐eq year −1 , with the largest contribution from N 2 O emissions. The sequestered SOC offset ~28% of the climate‐warming effects resulting from non‐CO 2 GHG emissions, and this offsetting effect increased over time. Increased nitrogen fertilizer use was the dominant factor contributing to the increase in net GHG emissions during 1960–2018, explaining ~47% of total changes. In contrast, reduced cropland area, the adoption of agricultural conservation practices (e.g., reduced tillage), and rising atmospheric CO 2 levels attenuated net GHG emissions from U.S. croplands. Improving management practices to mitigate N 2 O emissions represents the biggest opportunity for achieving net‐zero emissions in U.S. croplands. Our study highlights the importance of concurrently quantifying SOC‐sequestered CO 2 and non‐CO 2 GHG emissions for developing effective agricultural climate change mitigation measures.

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Spillway deflector designs for mitigating supersaturated total dissolved gases - Pengcheng Li; David Z. Zhu; James Crossman; Xiaolong Cheng (Journal of Cleaner Production, 2023)

A critical review on the evaluation of toxicity and ecological risk assessment of plastics in the marine environment - David Leistenschneider; Adèle Wolinski; Jingguang Cheng; Alexandra ter Halle; Guillaume Duflos; Arnaud Huvet; Ika Paul-Pont; Franck Lartaud; François Galgani; Édouard Lavergne; Anne-Leila Meistertzheim; Jean-François Ghiglione (Science of The Total Environment, 2023)

Enterohemorrhagic Escherichia coli O157:H7 antigens produced in transgenic lettuce effective as an oral vaccine in mice - Yun-Lin Su; Mariano Larzábal; Huan Song; Tianfang Cheng; Yufang Wang; Libia Yael Smith; Angel Adrian Cataldi; David W. Ow (Theoretical and Applied Genetics, 2023)

Plant genome resequencing and population genomics: Current status and future prospects - Bo Song; Weidong Ning; Di Wei; Mengyun Jiang; Kun Zhu; Xingwei Wang; David Edwards; Damaris A. Odeny; Shifeng Cheng (Molecular Plant, 2023)

Physicochemical and preservative properties of tyrosinase-crosslinked sodium caseinate-EGCG-carboxymethyl chitosan composite packaging: Comparison of blended and layer-by-layer films - Wenhan Xu; Wenzhang Chen; Qiankun Wang; David Julian McClements; Shuai Chen; Yutang Wang; Xuebo Liu; Cheng Wang; Fuguo Liu (Food Bioscience, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Basic human values of dairy producers in Canada and the U.S.: A cross-sectional survey study - Ting-Yu Cheng; Devon J. Wilson; Cecilia Brooks; Jessica A. Pempek; Kelly A. George; Stephen J. LeBlanc; Claudia Cobo-Angel; David L. Renaud; Gregory G. Habing (Journal of Rural Studies, 2023)

Discovery and exploration of monosaccharide linked dimers of galectin-3 inhibitors to target fibrosis - Jacob J. Swidorski; Brett R. Beno; Chunjian Liu; David S. Yoon; Kaushik Ghosh; Harinath Sale; Devang Shah; Kriti Acharya; Joseph Yanchunas; Priyanka Haldar; Narasimharaju Kalidindi; Jinal K. Shukla; et al. (Medicinal Chemistry Research, 2023)

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

mTOR pathway candidate genes and obesity interaction on breast cancer risk in black women from the Women’s Circle of Health Study - Mmadili N. Ilozumba; Lusine Yaghjyan; Susmita Datta; Jinying Zhao; Chi-Chen Hong; Kathryn L. Lunetta; Gary Zirpoli; Elisa V. Bandera; Julie R. Palmer; Song Yao; Christine B. Ambrosone; Ting-Yuan David Cheng (Cancer Causes & Control, 2023)

Development and characterization of active starch-based films incorporating graphene/polydopamine/Cu2+ nanocomposite fillers - Hao Xu; Long Chen; David Julian McClements; Hao Cheng; Jie Long; Zhengyu Jin (Carbohydrate Polymers, 2023)

Festuca apennina × F. pratensis triploid hybrids exceed their parents in adaptation to broad-environmental conditions - Beat Boller; Manuel K. Schneider; Cheng Zhao; Jan Bartoš; Joanna Majka; David Kopecky (Alpine Botany, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Investigation of a novel smart and active packaging materials: Nanoparticle-filled carrageenan-based composite films - Yahong Han; Mingrui Zhou; David Julian McClements; Fuguo Liu; Cheng Cheng; Jinwei Xiong; Ming Zhu; Shuai Chen (Carbohydrate Polymers, 2023)

Structure and properties of flexible starch-based double network composite films induced by dopamine self-polymerization - Hao Xu; Long Chen; Zhenlin Xu; David Julian McClements; Hao Cheng; Chao Qiu; Jie Long; Hangyan Ji; Man Meng; Zhengyu Jin (Carbohydrate Polymers, 2023)

Origin and evolution of a CO2-Rich gas reservoir offshore Angola: Insights from the Gas Composition and isotope analysis - Junjie Liu; Magali Pujol; Honggang Zhou; David Selby; Jie Li; Bin Cheng (Applied Geochemistry, 2023)

Late Carboniferous back-arc rifting in Junggar Basin, NW China: implication for the rapid continental growth in accretionary orogens - Wenbin Tang; Xiaojun Wang; Xuguang Guo; Wenjun He; Yong Tang; Georgia Pe-Piper; David J. W. Piper; Zhaojie Guo; Feng Cheng; Wei Li; Yuanyuan Zhang (International Journal of Earth Sciences, 2022)

A Non-destructive Quantitative Transmission Raman Spectroscopy Method for Active Pharmaceutical Ingredient in Drug Product In-Use Samples Prepared in Dosing Vehicles - Gregory Doddridge; Edwin Hong; David Cheng Thiam Tan; Yemin Liu (AAPS PharmSciTech, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

In search of a unifying criterion for meandering systems: examples from natural and built environments - Dork Sahagian; Panayiotis Diplas; Casey Urban; Zhihao Cheng; Madeline David (Environmental Fluid Mechanics, 2022)

Hydrodynamic Performance of Full-Scale T0 and T90 Codends with and without a Codend Cover - Zhaohai Cheng; Paul D. Winger; Shannon M. Bayse; David Kelly (Journal of Marine Science and Engineering, 2022)
The hydrodynamic performance of one full-scale T0 (mesh size 90 mm) and three T90 (mesh size 90, 100, and 110 mm) codends was investigated and compared using flume tank testing, with and without a small-mesh cover. We evaluated how flow velocity, mesh circularity, and drag changed in each codend at five different towing speeds (0.5–0.9 m/s). The results demonstrated that flow velocity decreased along the length of a codend, and this effect was pronounced in the T0 codend. Increasing the mesh size of T90 codends from 90 to 110 mm did not significantly affect flow velocity. A novel parameter, termed mesh circularity, was developed and introduced to describe mesh opening. Mesh circularity in the T0 codend decreased along the length of the codend, which contrasted with the T90 codends. Results showed that the T90 codends maintained relatively open meshes (circularity ranged from ~0.8 to 1.0 along the length of the codend) compared to the T0 (circularity ranged from ~0.6 to 0.4). Each T90 codend had a significantly (p 0.05), but was significantly different for the T90 codend (p

An Image Quality Comparison Study Between Homemade and Commercial Dental Cone-Beam CT Systems - Trang Thi Ngoc Tran; David Shih-Chun Jin; Kun-Long Shih; Ming-Lun Hsu; Jyh-Cheng Chen (Journal of Medical and Biological Engineering, 2021)
Purpose Cone-beam computed tomography (CBCT) has been widely applied in dental and maxillofacial imaging. Several dental CBCT systems have been recently developed in order to improve the performance. This study aimed to evaluate the image quality of our prototype (YMU-DENT-P001) and compare with a commercial POYE Expert 3DS dental CBCT system (system A). Methods The Micro-CT Contrast Scale, Micro-CT Water and Micro-CT HA phantoms were used to evaluate the two CBCT systems in terms of contrast-to-noise ratio (CNR), signal-to-noise ratio (SNR), uniformity (U), distortion, and linearity in the relationship between image intensity and calcium hydroxyapatite concentration. We also fabricated a proprietary thin-wire phantom to evaluate full width at half maximum (FWHM) spatial resolution. Both CBCT systems used the same exposure protocol, and data analysis was performed in accordance with ISO standards using a proprietary image analysis platform. Results The SNR of our prototype system was nearly five times higher than that of system A (prototype: 159.85 ± 3.88; A: 35.42 ± 0.61; p < 0.05) and the CNR was three times higher (prototype: 329.39 ± 5.55; A: 100.29 ± 2.31; p < 0.05). The spatial resolution of the prototype (0.2446 mm) greatly exceeded that of system A (0.5179 mm) and image distortion was lower (prototype: 0.03 mm; system A: 0.285 mm). Little difference was observed between the two systems in terms of the linear relationship between bone mineral density (BMD) and image intensity. Conclusions Within the scope of this study, our prototype YMU-DENT-P001 outperformed system A in terms of spatial resolution, SNR, CNR, and image distortion.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

HDAC inhibitors improve CRISPR-mediated HDR editing efficiency in iPSCs - Jian-Ping Zhang; Zhi-Xue Yang; Feng Zhang; Ya-Wen Fu; Xin-Yue Dai; Wei Wen; Beldon Zhang; Hannah Choi; Wanqiu Chen; Meredith Brown; David Baylink; Lei Zhang; et al. (Science China Life Sciences, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Apatite as an alternative petrochronometer to trace the evolution of magmatic systems containing metamict zircon - Hao-Cheng Yu; Kun-Feng Qiu; Callum J. Hetherington; David Chew; Ya-Qi Huang; Deng-Yang He; Jian-Zhen Geng; Hai-Yang Xian (Contributions to Mineralogy and Petrology, 2021)

New combinations and typifications in Haplopteris (Pteridaceae: Vittarioideae) - Cheng-Wei Chen; Stuart Lindsay; David J. Middleton; Daniele Cicuzza; Eric Schuettpelz (Kew Bulletin, 2021)

Response of non-point source pollution to landscape pattern: case study in mountain-rural region, China - Wuhua Li; Xiangju Cheng; Yu Zheng; Chengguang Lai; David J. Sample; Dantong Zhu; Zhaoli Wang (Environmental Science and Pollution Research, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Neuronal Protein Farnesylation Regulates Hippocampal Synaptic Plasticity and Cognitive Function - Wenhui Qu; Kiall F. Suazo; Wenfeng Liu; Shaowu Cheng; Angela Jeong; David Hottman; Li-Lian Yuan; Mark D. Distefano; Ling Li (Molecular Neurobiology, 2021)

An update of the Worldwide Integrated Assessment (WIA) on systemic insecticides. Part 2: impacts on organisms and ecosystems - Lennard Pisa; Dave Goulson; En-Cheng Yang; David Gibbons; Francisco Sánchez-Bayo; Edward Mitchell; Alexandre Aebi; Jeroen van der Sluijs; Chris J. K. MacQuarrie; Chiara Giorio; Elizabeth Yim Long; Melanie McField; et al. (Environmental Science and Pollution Research, 2021)
New information on the lethal and sublethal effects of neonicotinoids and fipronil on organisms is presented in this review, complementing the previous Worldwide Integrated Assessment (WIA) in 2015. The high toxicity of these systemic insecticides to invertebrates has been confirmed and expanded to include more species and compounds. Most of the recent research has focused on bees and the sublethal and ecological impacts these insecticides have on pollinators. Toxic effects on other invertebrate taxa also covered predatory and parasitoid natural enemies and aquatic arthropods. Little new information has been gathered on soil organisms. The impact on marine and coastal ecosystems is still largely uncharted. The chronic lethality of neonicotinoids to insects and crustaceans, and the strengthened evidence that these chemicals also impair the immune system and reproduction, highlights the dangers of this particular insecticidal class (neonicotinoids and fipronil), with the potential to greatly decrease populations of arthropods in both terrestrial and aquatic environments. Sublethal effects on fish, reptiles, frogs, birds, and mammals are also reported, showing a better understanding of the mechanisms of toxicity of these insecticides in vertebrates and their deleterious impacts on growth, reproduction, and neurobehaviour of most of the species tested. This review concludes with a summary of impacts on the ecosystem services and functioning, particularly on pollination, soil biota, and aquatic invertebrate communities, thus reinforcing the previous WIA conclusions (van der Sluijs et al. 2015).

Level of in vitro storage of the European catfish (Silurus glanis L.) eggs at different temperatures - Merve Tinkir; Devrim Memiş; Yu Cheng; Miaomiao Xin; Marek Rodina; David Gela; Vladimíra Tučková; Otomar Linhart (Fish Physiology and Biochemistry, 2021)

Archaeobotanical evidence reveals the human–environment interactions during the 9th–13th centuries at Turpan, Xinjiang on the ancient Silk Road - Yi-Feng Yao; Xia Wang; Wu Guo; Hong-En Jiang; Min Li; David K. Ferguson; Yu-Fei Wang; Cheng-Sen Li (Vegetation History and Archaeobotany, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Himalayan wolf distribution and admixture based on multiple genetic markers - Geraldine Werhahn; Yanjiang Liu; Yao Meng; Chen Cheng; Zhi Lu; Luciano Atzeni; Zhixiong Deng; Shi Kun; Xinning Shao; Qi Lu; Jyoti Joshi; Adarsh Man Sherchan; et al. (Journal of Biogeography, 2020)
Aim We explore the phylogeography of Himalayan wolves using multiple genetic markers applied on a landscape‐scale dataset and relate our findings to the biogeographic history of the region. Location Himalayas of Nepal, the Tibetan Plateau of China and mountain ranges of Central Asia. Taxon Himalayan wolf (also called the Tibetan wolf), Canis lupus chanco . Methods We present a large‐scale, non‐invasive study of Himalayan wolves from across their estimated range. We analysed 280 wolf scat samples from western China, Kyrgyzstan and Tajikistan at two mtDNA loci, 17 microsatellite loci, four non‐synonymous SNPs in three nuclear genes related to the hypoxia pathway, and ZF genes on both sex chromosomes. Results Our results corroborate previous studies showing that the Himalayan wolf forms a distinct lineage adapted to high altitudes in excess of 4,000 m elevation. We found a correlation between hypoxia adaptation and the divergent Himalayan wolf mtDNA haplotype found across the Tibetan Plateau of Qinghai, the Tibetan Autonomous Region and the Nepalese Himalayas. We identified a region of admixture between Himalayan and grey wolves at the boundary of their distributions, where the Tibetan Plateau elevation gradually drops. Main Conclusion Based on multiple genetic markers, the Himalayan wolf forms a reciprocally monophyletic lineage with a unique adaptation to high altitude. We propose that the divergence of the lineage is related to past uplift of the region, and that the lineage maintains its high‐altitude niche, in part, by means of its genetic adaptation to hypoxia. We conclude that the Himalayan wolf merits taxonomic recognition and designation as an evolutionary significant unit (ESU).

Pharmacokinetics and pharmacodynamics of three oral formulations of curcumin in rats - Lujing Wang; Wenji Li; David Cheng; Yue Guo; Renyi Wu; Ran Yin; Shanyi Li; Hsiao-Chen Kuo; Rasika Hudlikar; Hilly Yang; Brian Buckley; Ah-Ng Kong (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Comparison between two kinds of natural pollen traps in tropical China: ants’ nests on tree branches versus surface soil - Zhi-Yong Zhang; Feng-Chun Yang; Dong-Mei Cheng; David K. Ferguson; Wan Hu; Yue-Zhuo Li; Cheng-Sen Li (Palynology, 2020)

The root endophytic fungus Serendipita indica improves resistance of Banana to Fusarium oxysporum f. sp. cubense tropical race 4 - Chunzhen Cheng; Dan Li; Quan Qi; Xueli Sun; Mensah Raphael Anue; Bodjrenou Mahoudjro David; Yongyan Zhang; Xiangyang Hao; Zihao Zhang; Zhongxiong Lai (European Journal of Plant Pathology, 2020)

Changes in area and number of nature reserves in China - Zhijun Ma; Ying Chen; David S. Melville; Jun Fan; Jianguo Liu; Jinwei Dong; Kun Tan; Xuefei Cheng; Richard A. Fuller; Xiangming Xiao; Bo Li (Conservation Biology, 2019)
Nature reserves (NR) are the cornerstone of biodiversity conservation. Over the past 60 years, the rapid expansion of NRs in China, one of the world's megadiverse countries, has played a critical role in slowing biodiversity loss. We examined the changes in the number and area of China's NRs from 1956 to 2014 and analyzed the effect of economic development on the expansion of China's NRs from 2005 to 2014 with linear models. Despite a continuing increase in the number of NRs, the total area of China's NRs decreased by 3% from 2007 to 2014. This loss resulted from downsizing and degazettement of existing NRs and a slowdown in the establishment of new ones. Nature reserves in regions with rapid economic development exhibited a greater decrease in area, suggesting that downsizing and degazettement of NRs are closely related to the intensifying competition between economic growth and conservation. For example, boundary adjustments to national NRs, the most strictly protected NRs, along the coast of China's Yellow Sea, a global biodiversity hotspot with a fast‐growing economy, resulted in the loss of one‐third of the total area. One of the most important ecosystems in these NRs, tidal wetlands, decreased by 27.8% because of boundary adjustments and by 25.2% because of land reclamation. Our results suggest conservation achievement, in terms of both area and quality, are declining at least in some regions in the Chinese NR estate. Although the designation of protected areas that are primarily managed for sustainable use has increased rapidly in recent years in China, we propose that NRs with biodiversity conservation as their main function should not be replaced or weakened.

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Associations between microplastic pollution and land use in urban wetland sediments - Kallie R. Townsend; Hsuan-Cheng Lu; David J. Sharley; Vincent Pettigrove (Environmental Science and Pollution Research, 2019)

Low-pressure–temperature stability of pyrope + quartz relative to orthopyroxene + kyanite: a new model for aluminous orthopyroxene with vacancies - Nanfei Cheng; David M. Jenkins; Timothy J. B. Holland (Contributions to Mineralogy and Petrology, 2019)

Subdividing the Holocene Series/Epoch: formalization of stages/ages and subseries/subepochs, and designation of GSSPs and auxiliary stratotypes - MIKE WALKER; Martin J. Head; John Lowe; Max Berkelhammer; Svante BjÖrck; Hai Cheng; Les C. Cwynar; David Fisher; Vasileios Gkinis; Antony Long; Rewi Newnham; Sune Olander Rasmussen; et al. (Journal of Quaternary Science, 2019)
The Holocene, which currently spans ~11 700 years, is the shortest series/epoch within the geological time scale (GTS), yet it contains a rich archive of evidence in stratigraphical contexts that are frequently continuous and often preserved at high levels of resolution. On 14 June 2018, the Executive Committee of the International Union of Geological Sciences formally ratified a proposal to subdivide the Holocene into three stages/ages, along with their equivalent subseries/subepochs, each anchored by a Global boundary Stratotype Section and Point (GSSP). The new stages are the Greenlandian (Lower/Early Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP2 ice core and dated at 11 700 a b2k (before 2000 CE); the Northgrippian (Middle Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP1 ice core and dated at 8236 a b2k; and the Meghalayan (Upper/Late Holocene Subseries/Subepoch) with its GSSP in a speleothem from Mawmluh Cave, north‐eastern India, with a date of 4250 a b2k. We explain the nomenclature of the new divisions, describe the procedures involved in the ratification process, designate auxiliary stratotypes to support the GSSPs and consider the implications of the subdivision for defining the Anthropocene as a new unit within the GTS.

Moringa Isothiocyanate Activates Nrf2: Potential Role in Diabetic Nephropathy - David Cheng; Linbo Gao; Shan Su; Davit Sargsyan; Renyi Wu; Ilya Raskin; Ah-Ng Kong (The AAPS Journal, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Impact of individual and neighborhood factors on socioeconomic disparities in localized and advanced prostate cancer risk - Mindy C. DeRouen; Clayton W. Schupp; Juan Yang; Jocelyn Koo; Andrew Hertz; Salma Shariff-Marco; Myles Cockburn; David O. Nelson; Sue A. Ingles; Iona Cheng; Esther M. John; Scarlett L. Gomez (Cancer Causes & Control, 2018)

Consistency of seven different GNSS global ionospheric mapping techniques during one solar cycle - David Roma-Dollase; Manuel Hernández-Pajares; Andrzej Krankowski; Kacper Kotulak; Reza Ghoddousi-Fard; Yunbin Yuan; Zishen Li; Hongping Zhang; Chuang Shi; Cheng Wang; Joachim Feltens; Panagiotis Vergados; et al. (Journal of Geodesy, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Resting GABA concentration predicts inhibitory control during an auditory Go-Nogo task - Chia-Hsiung Cheng; David M. Niddam; Shih-Chieh Hsu; Chia-Yih Liu; Shang-Yueh Tsai (Experimental Brain Research, 2017)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Serum 25-hydroxyvitamin D concentrations and lung cancer risk in never-smoking postmenopausal women - Ting-Yuan David Cheng; Xiaoling Song; Shirley A. A. Beresford; Gloria Y. F. Ho; Karen C. Johnson; Mridul Datta; Rowan T. Chlebowski; Jean Wactawski-Wende; Lihong Qi; Marian L. Neuhouser (Cancer Causes & Control, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Benign breast disease and risk of thyroid cancer - Juhua Luo; Michael Hendryx; Rami Nassir; Ting-Yuan David Cheng; Dorothy Lane; Karen L. Margolis (Cancer Causes & Control, 2017)

Laser Sintered Porous Ti–6Al–4V Implants Stimulate Vertical Bone Growth - Alice Cheng; David J. Cohen; Adrian Kahn; Ryan M. Clohessy; Kaan Sahingur; Joseph B. Newton; Sharon L. Hyzy; Barbara D. Boyan; Zvi Schwartz (Annals of Biomedical Engineering, 2017)

Submicron size-scale mapping of carbonate effective elastic properties from FIB-SEM images and finite element method - HuiHong Cheng; BoJing Zhu; David A. Yuen; YaoLin Shi (Science China Earth Sciences, 2017)

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

A numerical study of the impact of hurricane-induced storm surge on the Herbert Hoover Dike at Lake Okeechobee, Florida - Yuepeng Li; Yi-Cheng Teng; David M. Kelly; Keqi Zhang (Ocean Dynamics, 2016)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Mycorrhizal fungi and roots are complementary in foraging within nutrient patches - Lei Cheng; Weile Chen; Thomas S. Adams; Xing Wei; Le Li; Michael Luke McCormack; Jared L. DeForest; Roger T. Koide; David M. Eissenstat (Ecology, 2016)
The roots of the majority of tree species are associated with either arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. The absorptive roots of tree species also vary widely in their diameter. The linkages between root thickness, mycorrhiza type and nutrient foraging are poorly understood. We conducted a large root ingrowth experiment in the field to investigate how absorptive roots of varying thickness and their associated fungi (AM vs. EM) exploit different nutrient patches (inorganic and organic) in a common garden. In nutrient‐rich patches, thin‐root tree species more effectively proliferated absorptive roots than thick‐root tree species, whereas thick‐root tree species proliferated more mycorrhizal fungal biomass than thin‐root tree species. Moreover, nutrient patches enriched with organic materials resulted in greater root and mycorrhizal fungal proliferation compared to those enriched with inorganic nutrients. Irrespective of root morphology, AM tree species had higher root foraging precision than mycorrhizal hyphae foraging precision within organic patches, whereas EM tree species exhibited the opposite. Our findings that roots and mycorrhizal fungi are complementary in foraging within nutrient patches provide new insights into species coexistence and element cycling in terrestrial ecosystems.

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Validation of the FAST forecast model for the storm surges due to hurricanes Wilma and Ike - David M. Kelly; Yi-Cheng Teng; Yuepeng Li; Keqi Zhang (Natural Hazards, 2016)

Genetic variants in the mTOR pathway and interaction with body size and weight gain on breast cancer risk in African-American and European American women - Ting-Yuan David Cheng; Jyoti Shankar; Gary Zirpoli; Michelle R. Roberts; Chi-Chen Hong; Elisa V. Bandera; Christine B. Ambrosone; Song Yao (Cancer Causes & Control, 2016)

Forelimb contractures and abnormal tendon collagen fibrillogenesis in fibulin-4 null mice - Dessislava Z. Markova; Te-Cheng Pan; Rui-Zhu Zhang; Guiyun Zhang; Takako Sasaki; Machiko Arita; David E. Birk; Mon-Li Chu (Cell and Tissue Research, 2016)

Trabecular Bone Morphological Analysis for Preclinical Osteoporosis Application Using Micro Computed Tomography Scanner - David Shih-Chun Jin; Chien-Hao Chu; Jyh-Cheng Chen (Journal of Medical and Biological Engineering, 2016)

Mercury in Forage Fish from Mexico and Central America: Implications for Fish-Eating Birds - John E. Elliott; David A. Kirk; Kyle H. Elliott; Jessica Dorzinsky; Sandi Lee; Ernesto Ruelas Inzunza; Kimberly M. T. Cheng; Tony Scheuhammer; Patrick Shaw (Archives of Environmental Contamination and Toxicology, 2015)

Chromosomal genomics facilitates fine mapping of a Russian wheat aphid resistance gene - Helena Staňková; Miroslav Valárik; Nora L. V. Lapitan; Paul J. Berkman; Jacqueline Batley; David Edwards; Ming-Cheng Luo; Zuzana Tulpová; Marie Kubaláková; Nils Stein; Jaroslav Doležel; Hana Šimková (Theoretical and Applied Genetics, 2015)

A Deep, Non-potable Water Supply for the Ochoa Sulphate of Potash (SOP) Mine Project, New Mexico, USA - Peter Castiglia; William Linderfelt; Cheng Cheng; Annelia Tinklenberg; David Jordan; Tim Dale; Randy Foote; Terre Lane (Mine Water and the Environment, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

Anther development of maize (Zea mays) and longstamen rice (Oryza longistaminata) revealed by cryo-SEM, with foci on locular dehydration and pollen arrangement - Chih-Hua Tsou; Ping-Chin Cheng; Chiung-Maan Tseng; Hsiao-Jung Yen; Yu-Lan Fu; Tien-Rong You; David B. Walden (Plant Reproduction, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Submicron volume roughness & asperity contact friction model for principle slip surface in flash heating process - Bojing Zhu; David A. Yuen; Yaolin Shi; Huihong Cheng (Journal of Earth Science, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Chronic cannabidiol treatment improves social and object recognition in double transgenic APPswe/PS1∆E9 mice - David Cheng; Jac Kee Low; Warren Logge; Brett Garner; Tim Karl (Psychopharmacology, 2014)

Synthesis of bufalin derivatives with inhibitory activity against prostate cancer cells - Xiao-Feng Yuan; Hai-Yan Tian; Juan Li; Lu Jin; Shu-Tai Jiang; Ken Wing-Keung Liu; Cheng Luo; David A. Middleton; Mikael Esmann; Wen-Cai Ye; Ren-Wang Jiang (Natural Product Research, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

High-Throughput Biophysical Analysis of Protein Therapeutics to Examine Interrelationships Between Aggregate Formation and Conformational Stability - Rajoshi Chaudhuri; Yuan Cheng; C. Russell Middaugh; David B. Volkin (The AAPS Journal, 2014)

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

ShakerIR and Kv1.5 mutant channels with enhanced slow inactivation also exhibit K+ o-dependent resting inactivation - Yen May Cheng; David Fedida; Steven J. Kehl (Pflügers Archiv - European Journal of Physiology, 2013)

The discovery of 3-(1-aminoethylidene)quinoline-2, 4(1H,3H)-dione derivatives as novel PSII electron transport inhibitors - Yu-Xiu Liu; Hua-Ping Zhao; Zi-Wen Wang; Yong-Hong Li; Hai-Bin Song; Hannah Riches; David Beattie; Yu-Cheng Gu; Qing-Min Wang (Molecular Diversity, 2013)

Medicago glucosyltransferase UGT72L1: potential roles in proanthocyanidin biosynthesis - Yongzhen Pang; Xiaofei Cheng; David V. Huhman; Junying Ma; Gregory J. Peel; Keiko Yonekura-Sakakibara; Kazuki Saito; Guoan Shen; Lloyd W. Sumner; Yuhong Tang; Jianqi Wen; Jianfei Yun; et al. (Planta, 2013)

Distribution and Removal of Silver and Lead in the Nearshore Waters of Western Taiwan - Cheng-Shiuan Lee; Ching-Ling Wei; Liang-Saw Wen; David D.-D. Sheu; Wen-Huei Lee (Estuaries and Coasts, 2013)

Biotic resistance in marine environments - David L. Kimbro; Brian S. Cheng; Edwin D. Grosholz (Ecology Letters, 2013)
Biological invasions depend in part on the resistance of native communities. Meta‐analyses of terrestrial experiments demonstrate that native primary producers and herbivores generally resist invasions of primary producers, and that resistance through competition strengthens with native producer diversity. To test the generality of these findings, we conducted a meta‐analysis of marine experiments. We found that native marine producers generally failed to resist producer invasions through competition unless the native community was diverse, and this diversity effect was weaker in marine than in terrestrial systems. In contrast, native consumers equally resisted invasive producers in both ecosystems. Most marine experiments, however, tested invasive consumers and these invasions were resisted more strongly than were producer invasions. Given these differences between ecosystems and between marine trophic levels, we used a model‐selection approach to assess if factors other than the resistance mechanism (i.e. competition vs. consumption) are more important for predicting marine biotic resistance. These results suggest that understanding marine biotic resistance depends on latitude, habitat and invader taxon, in addition to distinguishing between competition with and consumption by native species. By examining biotic resistance within and across ecosystems, our work provides a more complete understanding of the factors that underlie biological invasions.

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Genetic diversity and population structure in wild Sichuan rhesus macaques - Di Yan Li; Huai Liang Xu; Jessica Satkoski Trask; Qing Zhu; An Chun Cheng; David Glenn Smith; Debbie George; Long Zhang (Molecular Biology Reports, 2013)

Ancient plant use at the site of Yuergou, Xinjiang, China: implications from desiccated and charred plant remains - Hongen Jiang; Yong Wu; Huanhuan Wang; David K. Ferguson; Cheng-Sen Li (Vegetation History and Archaeobotany, 2013)

Recent emergence of the wheat Lr34 multi-pathogen resistance: insights from haplotype analysis in wheat, rice, sorghum and Aegilops tauschii - Simon G. Krattinger; David R. Jordan; Emma S. Mace; Chitra Raghavan; Ming-Cheng Luo; Beat Keller; Evans S. Lagudah (Theoretical and Applied Genetics, 2013)

Field response of aboveground non-target arthropod community to transgenic Bt-Cry1Ab rice plant residues in postharvest seasons - Yao-Yu Bai; Rui-Hong Yan; Gong-Yin Ye; Fangneng Huang; David S. Wangila; Jin-Jun Wang; Jia-An Cheng (Transgenic Research, 2012)

Intracellular-signaling tumor-regression modeling of the pro-apoptotic receptor agonists dulanermin and conatumumab - Brittany P. Kay; Cheng-Pang Hsu; Jian-Feng Lu; Yu-Nien Sun; Shuang Bai; Yan Xin; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Serum 25-hydroxyvitamin D, vitamin A, and lung cancer mortality in the US population: a potential nutrient–nutrient interaction - Ting-Yuan David Cheng; Marian L. Neuhouser (Cancer Causes & Control, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Vegetation and climate of the Lop Nur area, China, during the past 7 million years - Hui Hao; David K. Ferguson; Hong Chang; Cheng-Sen Li (Climatic Change, 2012)

Initiation of segmental locomotor-like activities by stimulation of ventrolateral funiculus in the neonatal rat - Jianguo Cheng; David S. K. Magnuson (Experimental Brain Research, 2011)

Comparison of a high-density genetic linkage map to genome features in the model grass Brachypodium distachyon - Naxin Huo; David F. Garvin; Frank M. You; Stephanie McMahon; Ming-Cheng Luo; Yong Q. Gu; Gerard R. Lazo; John Philip Vogel (Theoretical and Applied Genetics, 2011)

Genomic analysis of Acidianus hospitalis W1 a host for studying crenarchaeal virus and plasmid life cycles - Xiao-Yan You; Chao Liu; Sheng-Yue Wang; Cheng-Ying Jiang; Shiraz A. Shah; David Prangishvili; Qunxin She; Shuang-Jiang Liu; Roger A. Garrett (Extremophiles, 2011)

Competitive protein adsorption on polysaccharide and hyaluronate modified surfaces - Michela Ombelli; Lauren Costello; Corinne Postle; Vinod Anantharaman; Qing Cheng Meng; Russell J. Composto; David M. Eckmann (Biofouling, 2011)

Iron uptake and toxin synthesis in the bloom‐forming Microcystis aeruginosa under iron limitation - Ralitza Alexova; Manabu Fujii; Debra Birch; Jennifer Cheng; T. David Waite; Belinda C. Ferrari; Brett A. Neilan (Environmental Microbiology, 2011)
Summary Toxin production during cyanobacterial blooms poses a significant public health threat in water bodies globally and requires the development of effective bloom management strategies. Previously, synthesis of the hepatotoxin microcystin has been proposed to be regulated by iron availability, but the contribution of the toxin to the adaptation of cyanobacteria to environmental stresses, such as changing light intensity and nutrient limitation, remains unclear. The aim of this study was to compare the iron stress response in toxic and non‐toxic strains of Microcystis aeruginosa subjected to moderate and severe iron limitation. The transcription of a number of genes involved in iron uptake, oxidative stress response, toxin synthesis and transcriptional control of these processes was accessed by quantitative real‐time PCR (qRT‐PCR). The process of adaptation of M. aeruginosa to iron stress was found to be highly dynamic and strain‐specific. Toxin production in PCC 7806 increased in an iron‐dependent manner and appeared to be regulated by FurA. The inability to produce microcystin, either due to natural mutations in the mcy gene cluster or due to insertional inactivation of mcyH , affected the remodelling of the photosynthetic machinery in iron‐stressed cells, the transport of Fe(II) and transcription of the Fur family of transcriptional regulators. The presence of the toxin appears to give an advantage to microcystin‐producing cyanobacteria in the early stages of exposure to severe iron stress and may protect the cell from reactive oxygen species‐induced damage.

Seismic monitoring of western Pacific typhoons - Wu-Cheng Chi; Wan-Jou Chen; Ban-Yuan Kuo; David Dolenc (Marine Geophysical Research, 2010)

Trophic ecology of the invasive argentine ant: spatio-temporal variation in resource assimilation and isotopic enrichment - Sean B. Menke; Andy V. Suarez; Chadwick V. Tillberg; Cheng T. Chou; David A. Holway (Oecologia, 2010)

Impacts of land use and water quality on macroinvertebrate communities in the Pearl River drainage basin, China - Yixin Zhang; David Dudgeon; Dongsheng Cheng; Wai Thoe; Lincoln Fok; Zaoyin Wang; Joseph H. W. Lee (Hydrobiologia, 2010)

Cancer risks from betel quid chewing beyond oral cancer: a multiple-site carcinogen when acting with smoking - Chi Pang Wen; Min Kuang Tsai; Wen Shen Isabella Chung; Hui Ling Hsu; Yen Chen Chang; Hui Ting Chan; Po Huang Chiang; Ting-Yuan David Cheng; Shan Pou Tsai (Cancer Causes & Control, 2010)

Loss of microbial (pathogen) infections associated with recent invasions of the red imported fire ant Solenopsis invicta - Chin-Cheng Yang; Yi-Chih Yu; Steven M. Valles; David H. Oi; Yin-Cheng Chen; DeWayne Shoemaker; Wen-Jer Wu; Cheng-Jen Shih (Biological Invasions, 2010)

Paleoenvironmental inferences from diatom assemblages of the middle Miocene Shanwang Formation, Shandong, China - Ya-Meng Li; David K. Ferguson; Yu-Fei Wang; Cheng-Sen Li (Journal of Paleolimnology, 2010)

An Early Pliocene lake and its surrounding vegetation in Zhejiang, East China - Jin-Feng Li; Ya-Qin Hu; David Kay Ferguson; Yu-Fei Wang; Cheng-Sen Li (Journal of Paleolimnology, 2010)

Early Paleocene vegetation and climate in Jiayin, NE China - Hui Hao; David K. Ferguson; Guang-Ping Feng; Albert Ablaev; Yu-Fei Wang; Cheng-Sen Li (Climatic Change, 2010)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Isolation of a low-sulfur tolerance gene from Eichhornia crassipes using a functional gene-mining approach - Xiao Liu; Xi Chen; David J. Oliver; Cheng-Bin Xiang (Planta, 2009)

Reconstruction of paleovegetation and paleoclimate in the Early and Middle Eocene, Hainan Island, China - Yi-Feng Yao; Subir Bera; David K. Ferguson; Volker Mosbrugger; Khum N. Paudayal; Jian-Hua Jin; Cheng-Sen Li (Climatic Change, 2009)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part II: future estimates - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part I: historical analysis - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

A Synoptic Climatological Approach to Assess Climatic Impact on Air Quality in South-central Canada. Part I: Historical Analysis - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; David Yap (Water, Air, & Soil Pollution, 2007)

A Synoptic Climatological Approach to Assess Climatic Impact on Air Quality in South-central Canada. Part II: Future Estimates - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; David Yap (Water, Air, & Soil Pollution, 2007)

The Reconstruction of Paleovegetation and Paleoclimate in the Late Pliocene of West Yunnan, China - Xiang-Yu Kou; David K. Ferguson; Jing-Xian Xu; Yu-Fei Wang; Cheng-Sen Li (Climatic Change, 2006)

A catalog of nonsynonymous polymorphism on mouse Chromosome 16 - Jeffrey M. Kidd; Karrie C. Trevarthen; David L. Tefft; Ze Cheng; Michaele Mooney; Mark D. Adams (Mammalian Genome, 2005)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Functional genomic analysis of Arabidopsis thaliana glycoside hydrolase family 1 - Zhiwei Xu; Luis Escamilla-Trevio; Lihui Zeng; Mallikarjun Lalgondar; David Bevan; Brenda Winkel; Ali Mohamed; Chi-Lien Cheng; Ming-Che Shih; Jonathan Poulton; Asim Esen (Plant Molecular Biology, 2004)

Effects of oxidant-induced injury on heme oxygenase and glutathione in cultured aortic endothelial cells from atherosclerosis-susceptible and -resistant Japanese quail - Kenneth A. Hoekstra; David V. Godin; Jamal Kurtu; Kimberly M. Cheng (Molecular and Cellular Biochemistry, 2003)

Heme oxygenase and antioxidant status in cultured aortic endothelial cells isolated from atherosclerosis-susceptible and -resistant Japanese quail - Kenneth A. Hoekstra; David V. Godin; Jamal Kurtu; Kimberley M. Cheng (Molecular and Cellular Biochemistry, 2003)

Alterations in aortic antioxidant components in an experimental model of atherosclerosis: A time-course study - David V. Godin; Cathleen R. Nichols; Kenneth A. Hoekstra; Maureen E. Garnett; Kimberly M. Cheng (Molecular and Cellular Biochemistry, 2003)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Illumination and turbidity effects on observing faceted bottom elements with uniform Lambertian albedos - Kendall L. Carder,; Cheng-Chien Liu,; Zhongping Lee,; David C. English,; James Patten,; F. Robert Chen,; James E. Ivey; Davis Curtiss O. (Limnology and Oceanography, 2003)
Aircraft images were collected near Lee Stocking Island (LSI), Bahamas, with wavelike features for bright sand bottoms during times when solar zenith angles were large. The image contrast between leading and trailing wave facets approached a 10–15% difference because of algae accumulations in wave troughs or topographic variations of the bottom. Reflectance contrast for blue light was greater than for red and green wavelengths when algae or detritus was present in the troughs. However, the contrast at green and red wavelengths was greater than at blue wavelengths when caused by the interplay between bottom topography and oblique illumination. A three‐dimensional backwards Monte Carlo (BMC) model was developed to evaluate the effect of oblique illumination on wavelike topographic features for various values of water clarity and bottom albedo. An inverse optical modeling approach, previously developed for flat, horizontally homogeneous bottoms, was applied to the BMC results. Bathymetric estimates for bright facets tilted 10° toward the sun were slightly smaller than actual depths, whereas shaded facet depth estimates were too high by about 5%. Larger errors were associated with albedo retrievals, where shaded facets produced albedo estimates up to 15% lower than actual values. Errors increased with tilt angles up to 20° but decreased with sea and sky turbidity. Averaging sunlit and shaded pixels before running the inverse model reduced the uncertainty of bathymetric and albedo estimates to about 2 and 5%, respectively, comparable to previous field evaluations of the inversion model.

Quantification of Wall Shear Stress in Large Blood Vessels Using Lagrangian Interpolation Functions with Cine Phase-Contrast Magnetic Resonance Imaging - Christopher P. Cheng; David Parker; Charles A. Taylor (Annals of Biomedical Engineering, 2002)

Modeling of cable vibration effects of cable-stayed bridges - S. H. Cheng; David T. Lau (Earthquake Engineering and Engineering Vibration, 2002)

Nostoc flagelliforme and faked items retailed in Hong Kong - Paul Pui-Hay But; Ling Cheng; Pui Kwan Chan; David Tai-Wai Lau; Joyce Wing-Hin But (Journal of Applied Phycology, 2002)

In Vivo Quantification of Blood Flow and Wall Shear Stress in the Human Abdominal Aorta During Lower Limb Exercise - Charles A. Taylor; Christopher P. Cheng; Leandro A. Espinosa; Beverly T. Tang; David Parker; Robert J. Herfkens (Annals of Biomedical Engineering, 2002)

Mucosal Uptake of Gabapentin (Neurontin) vs. Pregabalin in the Small Intestine - Nusara Piyapolrungroj; Cheng Li; Howard Bockbrader; Guangyu Liu; David Fleisher (Pharmaceutical Research, 2001)

Tissue Remodeling of Rat Pulmonary Artery in Hypoxic Breathing. II. Course of Change of Mechanical Properties - Wei Huang; David Delgado-West; Jonathan T. Wu; Yuan Cheng Fung (Annals of Biomedical Engineering, 2001)

Tissue Remodeling of Rat Pulmonary Artery in Hypoxic Breathing. I. Changes of Morphology, Zero-Stress State, and Gene Expression - Wei Huang; Yuh-Pyng Sher; David Delgado-West; Jonathan T. Wu; Konan Peck; Yuan Cheng Fung (Annals of Biomedical Engineering, 2001)

cDNA cloning and characterization of a plant protein that may be associated with the harpinPSS-mediated hypersensitive response - Cheng-hsien Chen; Hao-jan Lin; Mang-jye Ger; David Chow; Teng-yung Feng (Plant Molecular Biology, 2000)

Regulation of Paracellular Absorption of Cimetidine and 5-Aminosalicylate in Rat Intestine - Simon Yuji Zhou; Nusara Piyapolrungroj; Li-heng Pao; Cheng Li; Guangyu Liu; Ellen Zimmermann; David Fleisher (Pharmaceutical Research, 1999)

Spatial Variability of Turbulent Fluxes in the Roughness Sublayer of an Even-Aged Pine Forest - Gabriel Katul; Cheng-I Hsieh; David Bowling; Kenneth Clark; Narasinha Shurpali; Andrew Turnipseed; John Albertson; Kevin Tu; Dave Hollinger; Bob Evans; Brian Offerle; Dean Anderson; et al. (Boundary-Layer Meteorology, 1999)

Meal Composition Effects on the Oral Bioavailability of Indinavir in HIV-Infected Patients - Peggy L. Carver; David Fleisher; Simon Y. Zhou; Daniel Kaul; Powel Kazanjian; Cheng Li (Pharmaceutical Research, 1999)

Transport of Pregabalin in Rat Intestine and Caco-2 Monolayers - Nancy Jezyk; Cheng Li; Barbra H. Stewart; Xiaochun Wu; Howard N. Bockbrader; David Fleisher (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Altered expression of sialylated carbohydrate antigens in HT29 colonic carcinoma cells - David R. Mack; Pi-Wan Cheng; Fulvio Perini; Shu Wei; Michael A. Hollingsworth (Glycoconjugate Journal, 1998)

Hydrogen peroxide-induced expression of the proto-oncogenes, c-jun, c-fos and c-myc in rabbit lens epithelial cells - David Wan-Cheng Li; Abraham Spector (Molecular and Cellular Biochemistry, 1997)

The traction effect of lateral roots of Pinus yunnanensis on soil reinforcement: a direct in situ test - Yue Zhou; David Watts; Xiaoping Cheng; Yuhui Li; Huasong Luo; Qian Xiu (Plant and Soil, 1997)

Distribution of specific apolipoproteins determined by immunoblotting of baboon lipoproteins resolved by polyacrylamide gradient gel electrophoresis - David L. Rainwater; Candace M. Kammerer; Min-Lee Cheng; Mary L. Sparks; John L. VandeBerg (Biochemical Genetics, 1992)

Distribution of specific apolipoproteins determined by immunoblotting of baboon lipoproteins resolved by polyacrylamide gradient gel electrophoresis - David L. Rainwater; Candace M. Kammerer; Min-Lee Cheng; Mary L. Sparks; John L. VandeBerg (Biochemical Genetics, 1992)